2021
DOI: 10.1038/s41598-021-98245-9
|View full text |Cite
|
Sign up to set email alerts
|

Normobaric oxygen treatment for mild-to-moderate depression: a randomized, double-blind, proof-of-concept trial

Abstract: Oxygen enriched air may increase oxygen pressure in brain tissue and have biochemical effects even in subjects without lung disease. Consistently, several studies demonstrated that normobaric oxygen treatment has clinical benefits in some neurological conditions. This study examined the efficacy of normobaric oxygen treatment in subjects with depression. In a randomized, double-blind trial, 55 participants aged 18–65 years with mild to moderate depression (had a Hamilton Rating Scale for Depression [HRSD] scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…On the other hand, the effects of O 2 on neuronal excitability in young healthy men were described as dose-dependent: 0.7 bar O 2 did not affect cFFF, 1.4 bar O 2 significantly jeopardized cFFFs, while 2.8 bar O 2 allowed for recovery of cFFF [50]. These results on oxygen are concerning, especially considering that normobaric oxygen is widely used in clinical settings [101,102], and a partial pressure of 1.4 bar is considered a safe upper limit for divers [103].…”
Section: Breathing Gasesmentioning
confidence: 99%
“…On the other hand, the effects of O 2 on neuronal excitability in young healthy men were described as dose-dependent: 0.7 bar O 2 did not affect cFFF, 1.4 bar O 2 significantly jeopardized cFFFs, while 2.8 bar O 2 allowed for recovery of cFFF [50]. These results on oxygen are concerning, especially considering that normobaric oxygen is widely used in clinical settings [101,102], and a partial pressure of 1.4 bar is considered a safe upper limit for divers [103].…”
Section: Breathing Gasesmentioning
confidence: 99%
“…The open-label design of the trial may also constitute a limitation since it is unknown whether changes in ACC connectivity may also occur in responders to placebo. The use of EMONO can be considered a limitation in that we cannot disentangle the speci c effect of N 2 O over oxygen and we cannot strictly ruled out the possibility that enriched oxygen have contributed to brain changes, especially because it has been found that repeated O2 can improve symptoms of depression [34]. However, N 2 O is considered a glutamate antagonist, unlike O2, which is highly concentrated in ACC and changes in the connectivity in this brain region may be more likely due to N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is increasingly used for preconditioning (even in combination with hypoxia) during sports training, for cardiovascular conditioning, or before extreme environmental stress, such as SCUBA diving, military free-fall or space flight, to reduce the chance of decompression sickness ( Webb and Pilmanis, 2011 ; Balestra et al, 2021 ; Lafère et al, 2021 ; Bestavashvili et al, 2022 ). Furthermore, many researchers point to the potential therapeutic application of oxygen therapy for depression or age-related neurological diseases such as Alzheimer’s disease ( Serebrovska et al, 2019 ; Bloch et al, 2021 ). One potential application of a hyperoxic environment has also been proposed even in an extraterrestrial application providing a slight increase in the partial pressure of O 2 on the Moon in underground tunnels to supply O 2 and compensate for the total pressure ( Martin and Benaroya, 2023 ).…”
Section: Introductionmentioning
confidence: 99%